Numerical forward modelling of 'fluxoturbidite' flume experiments using Sedsim - Huang, X.; Dyt, C.; Griffiths, Cedric; Salles, T. (Elsevier, 2012)
Delta front 'fluxoturbidity deposits' in rift basin margins, as well as sand avalanches, are influenced by topography, water level fluctuation and wave action. Instability of prior sediments deposited on the delta front is a prerequisite for the generation of 'fluxoturbidity'. In this study Sedsim, a three-dimensional numerical stratigraphic forward model is used to replicate and extend a set of physical flume tank experiments investigating the formation of 'fluxoturbidites' from different initial conditions. This study has investigated the influence of topographic slope, relative water level change and wave action on the formation of 'fluxoturbidites', and hopefully improves our understanding and insight into the dynamic processes of 'fluxoturbidity' resulting from different initiation mechanisms. The study also illustrates the value of numerical modelling in complementing and extending physical flume tank studies. We show that, at least at the scale of a flume tank, there exists an optimum window of topographic slopes within which 'fluxoturbidites' arise due to slumping. This window, ranging from 9° to 18°, may be useful in distinguishing the effects of topographic slope from other 'fluxoturbidite' causal mechanisms. The amplitude and frequency of water level oscillation appears to be a significant control on 'fluxoturbidite' thickness, while wave attributes, especially wave angles, appear to affect 'fluxoturbidite' locality relative to the sediment source.